Region-Based Lymphatic Filariasis Elimination in Indonesia: A Review of the Bounce Back Case in Pekalongan Regency - Firmansyah, Yura Witsqa; Lewinsca, Maurend Yayank; Husna, Riyana; Zolanda, Annisa; Iryanto, Andika Agus; Fuadi, Mirza Fathan; Ramadhansyah, Muhammad Fadli; Hardiyanto, Afdal; Sukaningtyas, Ramadani; Pratama, Aziz Yulianto; Hendrawan, Danang (Universitas Aisyah Pringsewu, 2021)
Indonesia has a variety of characteristics, environmental issues, and different Social Determinant of Health (SDH). Indonesia is currently the highest contributor to lymphatic filariasis cases in Southeast Asia. Mapping of lymphatic filariasis endemic areas has been carried out by the government with a management approach to eliminating lymphatic filariasis and it has the possibility of bounce back in endemic areas, lymphatic filariasis is a tropical disease that has been neglected along with the development of COVID-19, which is the government's priority so that an area-based management approach is needed. efforts to prioritize the elimination of lymphatic filariasis in Indonesia. This review aims to illustrate the region-based elimination of lymphatic filariasis in Indonesia.Abstrak: Indonesia memiliki keberagaman karakteristik, isu lingkungan, Social Determinant of Health (SDH) yang berbeda-beda. Indonesia saat ini menjadi kontributor tertinggi kasus Filariasis limfatik di Asia Tenggara. Pemetaan daerah endemis filariasis limfatik telah dilakukan pemerintah dengan upaya pendekatan manajemen eliminasi filariasis limfatik dan memiliki kemungkinan terjadinya bounce back pada daerah endemik, filariasis limfatik termasuk penyakit tropis yang terabaikan seiring dengan berkembangnya penyakit COVID-19 yang menjadi prioritas pemerintah sehingga perlu pendekatan manajemen berbasis wilayah dalam upaya memprioritaskan eliminasi filariasis limfatik di Indonesia. Ulasan ini bertujuan untuk gambaran menggambarkan eliminasi filariasis limfatik berbasis wilayah di Indonesia.